Magnetic assembly and method of manufacturing the same
Patent Information
- Application Number
- CN202611291525.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-30
AI Technical Summary
然而,高致密度的磁性组件直流偏置特性较差,劣化电子产品的寿命
[0047]本发明实施例提供的一种磁性组件及其制备方法,通过两种磁性粉末的粒度级配,能够改善磁性组件的磁性粉末颗粒间空隙填充效果,且细颗粒的加入为磁性组件提供了更高的矫顽力,从而在相同磁导率下有效降低了磁性组件的损耗并提升了其直流偏置性能。
Smart Images

Figure CN123017666A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of magnetic materials, and more particularly to a magnetic component and its preparation method. Background Technology
[0002] In modern high-frequency electronic equipment, magnetic components are widely used as core magnetic elements in fields such as switching power supplies, power factor correction (PFC) inductors, filter inductors, and electromagnetic compatibility (EMC) components.
[0003] As electronic products evolve towards higher frequencies, smaller sizes, and higher efficiency, higher demands are placed on the performance of magnetic materials. For example, high-density magnetic components (i.e., the close packing of powder particles) can increase the effective magnetic material content per unit volume, thereby enhancing the saturation magnetic induction and ensuring the stability of devices under high current conditions. However, high-density magnetic components have poor DC bias characteristics, which degrades the lifespan of electronic products.
[0004] Therefore, it is urgent to balance reducing the loss of magnetic components and improving DC bias characteristics under the same permeability conditions. Summary of the Invention
[0005] This invention provides a magnetic component and its preparation method. The magnetic component includes magnetic powder. By setting magnetic powders with different particle size characteristics to work together, the particle packing characteristics of the magnetic component are optimized, which provides a basis for loss control and DC bias performance improvement.
[0006] This invention provides a magnetic component, including magnetic powder;
[0007] The magnetic powder includes a first magnetic powder and a second magnetic powder;
[0008] The particle size of the first magnetic powder is ≤10μm;
[0009] The particle size of the second magnetic powder is >10 μm;
[0010] In the cross-sectional scanning electron microscope image of the magnetic component, the number of particles of the first magnetic powder with a particle size of 1μm to 10μm is ≥10 in at least 10 non-completely repeating 50μm×50μm regions.
[0011] In some embodiments of the present invention, the first magnetic powder includes a first core and a first coating layer disposed on at least a portion of the surface of the first core;
[0012] And / or, the second magnetic powder includes a second core and a second coating layer disposed on at least a portion of the surface of the second core;
[0013] And / or, the particle size range of the first magnetic powder is 1 μm to 10 μm;
[0014] And / or, the D50 of the second magnetic powder is 20μm~40μm.
[0015] In some embodiments of the present invention, the first core comprises at least one of an iron-silicon alloy material and an iron-silicon-aluminum alloy material;
[0016] And / or, the second core comprises an iron-silicon-aluminum alloy material;
[0017] And / or, the first coating layer includes one or more elements selected from C, O, and Si;
[0018] And / or, the first coating layer comprises phosphate;
[0019] And / or, the second coating layer comprises phosphate;
[0020] And / or, the thickness of the first coating layer is 50nm~500nm;
[0021] And / or, the thickness of the second coating layer is 0.1 μm to 0.5 μm.
[0022] In some embodiments of the present invention, the mass percentage of Fe element in the iron-silicon alloy material is 85wt%~98wt%;
[0023] And / or, the mass percentage of Si in the iron-silicon alloy material is 2wt%~15wt%;
[0024] And / or, the mass percentage of Fe in the iron-silicon-aluminum alloy material is 80wt%~90wt%;
[0025] And / or, the mass percentage of Si element in the iron-silicon-aluminum alloy material is 5wt%~12wt%;
[0026] And / or, the mass percentage of Al element in the iron-silicon-aluminum alloy material is 5wt%~12wt%.
[0027] In some embodiments of the present invention, the mass percentage of C element in the first coating layer is 0wt%~1wt%;
[0028] And / or, the mass percentage of O element in the first coating layer is 3wt%~8wt%;
[0029] And / or, the mass percentage of Si element in the first coating layer is 9wt%~20wt%;
[0030] And / or, the mass percentage of Fe in the iron-silicon alloy material is 95.2 wt% to 97.2 wt%;
[0031] And / or, the mass percentage of Si element in the iron-silicon alloy material is 2.8wt%~4.8wt%;
[0032] And / or, the mass percentage of Fe in the iron-silicon-aluminum alloy material is 84.6 wt% to 85.6 wt%;
[0033] And / or, the mass percentage of Si element in the iron-silicon-aluminum alloy material is 9.2wt%~9.8wt%;
[0034] And / or, the mass percentage of Al element in the iron-silicon-aluminum alloy material is 5.2wt%~5.6wt%.
[0035] In some embodiments of the present invention, in the scanning electron microscope image of the cross-section of the magnetic component, the number of the first magnetic powder particles with a particle size of 1 μm to 10 μm is ≥15 in at least 10 incompletely repeated 50 μm × 50 μm regions.
[0036] This invention also provides a method for preparing the magnetic component as described above, comprising the following steps:
[0037] The magnetic component is obtained by pressing a raw material system comprising a first powder material and a second powder material; the particle size of the first powder material is ≤10μm; and the D50 of the second powder material is >10μm.
[0038] In some embodiments of the present invention, the D50 of the second powder raw material is 20μm~40μm;
[0039] And / or, the first powder raw material accounts for 5wt% to 30wt% of the total mass of the first powder raw material and the second powder raw material;
[0040] And / or, the processing pressure of the pressing process is 200MPa~2000MPa;
[0041] And / or, the processing time for the pressing process is 10s to 60s.
[0042] In some embodiments of the present invention, the raw material system further includes a binder, which includes one or more of epoxy resin, silicone resin, polyimide resin, phenolic resin, and polyvinyl alcohol;
[0043] And / or, the raw material system further includes a binder, the binder accounting for 0.5wt% to 3wt% of the total mass of the magnetic powder;
[0044] And / or, the D50 of the second powder raw material is 20μm~30μm;
[0045] And / or, the first powder raw material accounts for 10wt% to 20wt% of the total mass of the first powder raw material and the second powder raw material;
[0046] And / or, the pressing pressure is 1000MPa~1500MPa. In some embodiments of the present invention, after the pressing process, the pressed product is further subjected to an annealing process, wherein the annealing temperature is 600℃~850℃ and the processing time is 0.5h~3h.
[0047] The present invention provides a magnetic component and its preparation method. By using two magnetic powders with different particle sizes, the gap filling effect between magnetic powder particles in the magnetic component can be improved. The addition of fine particles provides the magnetic component with higher coercivity, thereby effectively reducing the loss of the magnetic component and improving its DC bias performance under the same permeability. Attached Figure Description
[0048] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0049] Figure 1 This is a scanning electron microscope (SEM) image of the cross-section of the magnetic component in Embodiment 1 of the present invention at a magnification of 200x;
[0050] Figure 2 This is a scanning electron microscope (SEM) image of the cross-section of the magnetic component in Embodiment 1 of the present invention at a magnification of 500x.
[0051] Figure 3 This is a scanning electron microscope (SEM) image of the cross-section of the magnetic component in Embodiment 1 of the present invention at 800x magnification;
[0052] Figure 4 This is a scanning electron microscope (SEM) image of the cross-section of the magnetic component in Comparative Example 1 of the present invention at a magnification of 200x.
[0053] The accompanying drawings have illustrated specific embodiments of the invention, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the invention in any way, but rather to illustrate the concept of the invention to those skilled in the art through reference to particular embodiments. Detailed Implementation
[0054] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0055] Magnetic component fabrication technology is widely used in high-frequency electronic devices such as switching power supplies, inductors, filters, and electromagnetic compatibility components. Its core objective is to fabricate magnetic components with low loss and high DC bias characteristics through magnetic powder molding. Currently used magnetic components suffer from insufficient density, affecting their loss and DC bias performance. Existing technologies attempt to improve density using smaller magnetic powder particles, which can improve the DC bias performance of magnetic components, but this increases the overall loss of the magnetic components.
[0056] Furthermore, existing technologies attempt to address these issues using particle size distribution, where the particle size differences between different powders are typically small, with the ratio of fine to coarse particles usually less than or equal to 1:2. The inventors have found that with this particle size distribution, fine particles struggle to fully penetrate the tiny gaps between larger particles, resulting in limited gap-filling efficiency. This makes it difficult to meet the requirements of high-power-density, small-volume magnetic components for low loss and high DC bias characteristics. Therefore, how to balance reducing magnetic component losses and improving DC bias performance while maintaining the same permeability has become a pressing technical problem in this field.
[0057] In view of this, embodiments of the present invention provide a magnetic component, including magnetic powder; the magnetic powder includes a first magnetic powder and a second magnetic powder; the particle size of the first magnetic powder is ≤10μm; the particle size of the second magnetic powder is ≥10μm; in at least 10 incompletely repeating 50μm×50μm regions in the cross-sectional scanning electron microscope image of the magnetic component, the number of particles of the first magnetic powder with a particle size of 1μm~10μm is ≥10.
[0058] The magnetic component of this invention is constructed using a dual-particle-size combination system. The particle size of the first magnetic powder is controlled to be no greater than 10 μm, allowing it to geometrically penetrate the interparticle gaps and local micropore regions formed between the particles of the second magnetic powder. The particle size of the second magnetic powder is controlled to be greater than 10 μm, and this second magnetic powder provides the magnetic source for most of the magnetic component. By analyzing at least 10 incompletely overlapping 50 μm × 50 μm regions in the cross-sectional scanning electron microscope image of the magnetic component, the number of first magnetic powder particles with a particle size of 1 μm to 10 μm is counted and limited to ≥10, thereby ensuring sufficient addition and uniform distribution of the first magnetic powder in the magnetic component. Furthermore, when the magnetic powder of this invention meets the above requirements, the reasonable blending of the first and second magnetic powders can retain a sufficient amount of distributed micro-gaps. The demagnetizing field generated by these micro-gaps suppresses magnetic saturation, mitigating the rapid decay of inductance with increasing DC current, thereby improving the DC bias performance of the magnetic component.
[0059] Specifically, after the first magnetic powder fills the gaps between the second magnetic powder, the filling ratio of effective magnetic material per unit volume increases, the magnetic flux path becomes more continuous, and the local demagnetizing field is reduced, making the saturation process of the magnetic component under a DC bias magnetic field slower and more uniform. Simultaneously, the second magnetic powder, as coarse particles, forms the main magnetic flux framework, while the first magnetic powder, as fine particles, fills the gaps and provides additional magnetization response. The two form a complementary structure—at zero bias, the second magnetic powder dominates the initial permeability; under DC bias, when the second magnetic powder tends to saturate, the first magnetic powder can still maintain a certain magnetization intensity, making the permeability decay curve of the magnetic component smoother, thereby comprehensively improving the DC bias characteristics.
[0060] Regarding losses, the particle size of the first magnetic powder is much smaller than that of the second magnetic powder, effectively filling the gaps formed by the accumulation of the second magnetic powder particles. This improves the filling coefficient of the magnetic component, enhances magnetic circuit continuity, and reduces magnetic reluctance caused by the presence of pores. The reduction in magnetic reluctance means a more uniform distribution of working magnetic flux density within the core under the same excitation conditions, which helps suppress the growth of hysteresis losses caused by localized magnetic flux concentration. Eddy current losses per particle are proportional to the square of the particle size, and since the particle size of the first magnetic powder is much smaller than that of the second magnetic powder, the eddy current losses of a single first magnetic powder particle are significantly reduced. Although the first magnetic powder may introduce an increase in eddy current losses due to its larger specific surface area, its reduction effect on hysteresis losses controls the total magnetic loss to a certain extent, significantly improving DC bias performance while keeping the total loss essentially unchanged or slightly increased. In summary, the first magnetic powder significantly improves DC bias performance by reducing eddy current losses per particle and controlling the increase in total hysteresis losses, while keeping the total loss essentially unchanged.
[0061] In some embodiments of the present invention, the first magnetic powder includes a first core and a first coating layer disposed on at least a portion of the surface of the first core, which is beneficial for further reducing eddy current losses of the magnetic powder. The first coating layer can either continuously cover the entire outer surface of the first core or cover a portion of the surface of the first core, as long as it can form effective isolation in the contact area of the magnetic powder, thereby further reducing conductive contact between magnetic powders and suppressing eddy current losses.
[0062] In some embodiments of the present invention, the second magnetic powder includes a second core and a second coating layer disposed on at least a portion of the surface of the second core, which is beneficial for further reducing eddy current losses of the magnetic powder. The second coating layer can either continuously cover the entire outer surface of the second core or cover a portion of the surface of the second core, as long as it can form effective isolation in the contact area of the magnetic powder, thereby further reducing conductive contact between magnetic powders and suppressing eddy current losses.
[0063] In some embodiments of the present invention, the core can be prepared by gas atomization, and the resulting particle shape can be spherical, near-spherical, flake-like, or irregular; the coating layer can be formed by chemical vapor deposition, sol-gel, or phosphate treatment, so that the coating layer and the core have good adhesion and uniform coverage.
[0064] In some embodiments, the particle size of the first magnetic powder ranges from 1 μm to 10 μm. When the particle size of the first magnetic powder ranges from 1 μm to 10 μm, the particles of the first magnetic powder can better enter the gaps between the second magnetic powders, while further addressing the issues of oxidation and insulation unevenness. This, in turn, helps to better reduce the loss of the magnetic component and improve DC bias performance at the same permeability, and ensures the effective conduct of subsequent tests. For example, the particle size range of the first magnetic powder can be, for instance, 1 μm, 4 μm, 7 μm, 10 μm, or any combination thereof.
[0065] In some embodiments, the D50 of the second magnetic powder is 20 μm to 40 μm. When the D50 of the second magnetic powder is 20 μm to 40 μm, it is beneficial to further form a suitable particle size gradient in the particle size distribution system, which can further improve the packing state of coarse and fine particles, resulting in higher density of the magnetic component. The particle surface in this particle size range has a moderate specific surface area, which is more conducive to achieving uniform coating of the insulating coating layer, further ensuring effective insulation isolation between particles, further suppressing eddy current losses, and further reducing the overall loss of the magnetic component. For example, the D50 of the second magnetic powder can be, for example, a range of 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, or any combination thereof.
[0066] This invention can utilize conventional testing methods and instruments to test the particle size distribution of particles in magnetic components. For example, quantitative detection of the particle size distribution across the cross-section of the magnetic component can be achieved using SEM combined with image processing software. The specific testing process includes the following steps: attaching the cross-sectional sample of the magnetic component to a conductive adhesive sample stage and performing gold sputtering for conductivity; capturing clear microscopic morphology images with a standard scale using a scanning electron microscope; importing the SEM morphology images into image processing software to calibrate the scale size; selecting manual Feret diameter measurement or automatic threshold segmentation statistical method based on the particle morphology to collect a large amount of particle size data; summarizing the particle size data to calculate D50 and the particle size distribution span. During the particle size distribution test of the magnetic component cross-section, multiple sets of parallel magnetic component samples are selected for fracture preparation. For each cross-sectional sample, multiple non-overlapping areas are selected to capture SEM images, avoiding random errors caused by local particle agglomeration; and particle size distribution statistical calculations are performed by integrating particle size test data from all fields of view. The results of multi-region cross-sectional particle size tests can corroborate each other, and can objectively reflect the overall size distribution and dispersion state of magnetic particles inside the matrix. The test results are valid within the experimental error range.
[0067] In some embodiments of the present invention, the first core comprises at least one of a ferrosilicon alloy material and a ferrosilicon aluminum alloy material. Specifically, the first core may be independently selected from either a ferrosilicon alloy material or a ferrosilicon aluminum alloy material, or may simultaneously comprise both ferrosilicon alloy and ferrosilicon aluminum alloy materials. Ferrosilicon alloy materials have higher saturation magnetic flux density, while ferrosilicon aluminum alloy materials have higher resistivity, which can further suppress high-frequency eddy current losses and further reduce the losses of magnetic components.
[0068] In some embodiments of the present invention, the second core comprises an iron-silicon-aluminum alloy material. This iron-silicon-aluminum alloy material possesses high resistivity, which can further suppress high-frequency eddy current losses, and also has higher saturation magnetic induction intensity, which can further reduce the losses of the magnetic components.
[0069] In some embodiments of the present invention, the first coating layer includes one or more elements selected from C, O, and Si. When the first coating layer includes one or more elements selected from C, O, and Si, it indicates that a composite insulating layer containing carbon, oxygen, and silicon is formed on its surface. This layer can be obtained by chemical vapor deposition, sol-gel, or other methods, thereby further reducing the weakening of the magnetic properties of the magnetic component by the non-magnetic layer while ensuring insulation.
[0070] In some embodiments of the present invention, the first coating layer comprises phosphate. When the first coating layer comprises phosphate, a more stable inorganic insulating layer can be constructed on the surface of the first core to further enhance interparticle resistance and better suppress high-frequency eddy current losses.
[0071] In some embodiments of the present invention, the second coating layer comprises phosphate. When the second coating layer comprises phosphate, a more stable inorganic insulating layer can be constructed on the surface of the second core to further enhance interparticle resistance and better suppress high-frequency eddy current losses.
[0072] This invention allows for the testing of the elemental composition and distribution of magnetic powders using conventional testing methods and instruments in the art. For example, a scanning electron microscope (SEM) equipped with an energy-dispersive X-ray spectrometer (EDS) can be used for qualitative and semi-quantitative analysis of the micro-area elemental composition of the magnetic powder. The specific testing process includes the following steps: fixing the magnetic powder sample to be tested on a sample stage coated with conductive adhesive; turning on the SEM power supply and EDS software; placing the prepared sample stage into the sample exchange chamber of the SEM, closing the chamber door, and performing a vacuum operation; obtaining a clear image of the sample surface morphology by adjusting the focus, astigmatism, brightness, and contrast; and using the following analysis modes: point analysis, line scan analysis, and area distribution analysis; and performing EDS acquisition, elemental confirmation, and quantitative analysis. The test results of the three modes—point analysis, line scan analysis, and area distribution analysis—can corroborate each other within the allowable error range.
[0073] In some embodiments of the present invention, the thickness of the first coating layer is 50 nm to 500 nm. By controlling the thickness of the first coating layer to be between 50 nm and 500 nm, a more continuous and appropriately thick coating layer can be formed on the surface of the first core. This further ensures insulation integrity, mitigates the problem of decreased magnetic volume fraction caused by excessive coating thickness, and further reduces eddy current losses of the magnetic component at the same permeability. For example, the thickness of the first coating layer can be, for instance, a range of 50 nm, 100 nm, 200 nm, 500 nm, or any combination thereof.
[0074] In some embodiments of the present invention, the thickness of the second coating layer is 0.1 μm to 0.5 μm. By controlling the thickness of the second coating layer to 0.1 μm to 0.5 μm, the first core can maintain more stable insulation during pressing and annealing, thus better reducing the risk of coating layer damage and short circuits. For example, the thickness of the second coating layer can be, for instance, a range of 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, or any combination thereof.
[0075] The embodiments of this invention can use conventional testing methods and instruments in the art to test the thickness of the coating layer. For example, a magnetic thickness gauge can be used to perform non-destructive measurement of the thickness of the insulating coating layer on the surface of magnetic particles. The specific testing includes the following steps: turning on the power of the magnetic thickness gauge; calibrating the magnetic thickness gauge using a standard sheet; uniformly selecting multiple measurement points on the sample surface, the distribution of which should represent the thickness of the entire coating layer; placing the probe vertically and stably on the measurement points, avoiding tilting which would affect measurement accuracy; and reading the measurement result after the displayed value stabilizes. Each measurement point should be measured multiple times, usually no less than three times, and the average value should be taken as the measured thickness at that point.
[0076] In some embodiments of the present invention, the mass percentage of Fe in the iron-silicon alloy material is 85wt% to 98wt%. Controlling the mass percentage of Fe in the iron-silicon alloy material to 85wt% to 98wt% can further provide a high saturation magnetic flux density for the magnetic component, thereby more effectively improving the anti-saturation capability of the magnetic component under a large DC bias magnetic field and delaying inductance decay. For example, the mass percentage of iron in the iron-silicon alloy material can be, for instance, 85wt%, 88wt%, 90wt%, 95wt%, 98wt%, or any combination thereof.
[0077] In some embodiments of the present invention, the mass percentage of Si in the iron-silicon alloy material is 2wt% to 15wt%. Controlling the mass percentage of Si in the iron-silicon alloy material within this range can further suppress eddy current losses in the magnetic components and further reduce energy losses under high-frequency operating conditions. For example, the mass percentage of Si in the iron-silicon alloy material can be 2wt%, 5wt%, 9wt%, 12wt%, 15wt%, or any combination thereof.
[0078] In some embodiments of the present invention, the mass percentage of Fe in the iron-silicon-aluminum alloy material is 80wt% to 90wt%. Controlling the mass percentage of Fe in the iron-silicon-aluminum alloy material to 80wt% to 90wt% allows the magnetic component to possess both high saturation magnetization and high resistivity, thereby further delaying saturation under DC bias conditions, improving inductance retention, and further effectively suppressing eddy current losses. For example, the mass percentage of Fe in the iron-silicon-aluminum alloy material can be, for instance, 80wt%, 83wt%, 85wt%, 88wt%, 90wt%, or any combination thereof.
[0079] In some embodiments of the present invention, the mass percentage of Si in the iron-silicon-aluminum alloy material is 5wt% to 12wt%. Controlling the mass percentage of Si in the iron-silicon-aluminum alloy material within this range can further improve the resistivity of the magnetic powder, further reduce its magnetocrystalline anisotropy, improve temperature stability, and is more conducive to reducing the loss of the magnetic components. For example, the mass percentage of Si in the iron-silicon-aluminum alloy material can be, for instance, 5wt%, 7wt%, 9wt%, 11wt%, 12wt%, or any combination thereof.
[0080] In some embodiments of the present invention, the mass percentage of Al in the iron-silicon-aluminum alloy material is 5wt% to 12wt%. Controlling the mass percentage of Al in the iron-silicon-aluminum alloy material within 5wt% to 12wt% is more beneficial for improving the DC bias performance of the magnetic components. For example, the mass percentage of Al in the iron-silicon-aluminum alloy material can be, for instance, 5wt%, 7wt%, 9wt%, 11wt%, 12wt%, or any combination thereof.
[0081] In some embodiments of the present invention, the mass percentage of carbon element in the first coating layer is 0 wt% to 1 wt%, which gives the coating layer superior flexibility. During pressing, it can further deform with the magnetic material particles without cracking, thus maintaining its insulation integrity and better reducing the loss of the magnetic component. For example, the mass percentage of carbon element in the first coating layer can be 0 wt%, 0.2 wt%, 0.5 wt%, 0.8 wt%, 1 wt%, or any combination thereof.
[0082] In some embodiments of the present invention, the mass percentage of oxygen (O) in the first coating layer is 3 wt% to 8 wt%. Controlling the mass percentage of O in the first coating layer to 3 wt% to 8 wt% improves the hydrophobicity of the first magnetic powder, making it less prone to moisture absorption and further enhancing the insulation performance of the magnetic component in high humidity environments. For example, the mass percentage of O in the first coating layer can be 3 wt%, 4 wt%, 5.5 wt%, 7 wt%, 8 wt%, or any combination thereof.
[0083] In some embodiments of the present invention, the mass percentage of Si element in the first coating layer is 9wt% to 20wt%, which is beneficial for further improving the stress concentration problem in the magnetic powder and for further reducing the loss of the magnetic component. For example, the mass percentage of Si element in the first coating layer can be 9wt%, 12wt%, 15wt%, 18wt%, 20wt%, or any combination thereof.
[0084] In some embodiments of the present invention, the preferred mass percentage of Fe in the iron-silicon alloy material is 95.2 wt% to 97.2 wt%. When the mass percentage of Fe in the iron-silicon alloy material is 95.2 wt% to 97.2 wt%, the saturation magnetic flux density in the iron-silicon alloy is significantly enhanced, and the DC bias performance is further optimized. For example, the mass percentage of iron in the iron-silicon alloy material can be, for example, 95.2 wt%, 95.7 wt%, 96.2 wt%, 96.7 wt%, 97.2 wt%, or any combination thereof.
[0085] In some embodiments of the present invention, the mass percentage of Si in the iron-silicon alloy material is preferably 2.8 wt% to 4.8 wt%. When the mass percentage of Si in the iron-silicon alloy material is 2.8 wt% to 4.8 wt%, eddy current losses in the magnetic components can be further reduced, thereby further reducing the total losses of the magnetic components. For example, the mass percentage of Si in the iron-silicon alloy material can be, for example, 2.8 wt%, 3.3 wt%, 3.8 wt%, 4.3 wt%, 4.8 wt%, or any combination thereof.
[0086] In some embodiments of the present invention, the preferred mass percentage of Fe in the iron-silicon-aluminum alloy material is 84.6 wt% to 85.6 wt%. When the mass percentage of Fe in the iron-silicon-aluminum alloy material is 84.6 wt% to 85.6 wt%, the hysteresis loss in the magnetic component is further reduced, further optimizing the loss characteristics and DC bias performance of the magnetic component. For example, the mass percentage of Fe in the iron-silicon-aluminum alloy material can be 84.6 wt%, 84.4 wt%, 85.1 wt%, 85.4 wt%, 85.6 wt%, or any combination thereof.
[0087] In some embodiments of the present invention, the mass percentage of Si in the iron-silicon-aluminum alloy material is preferably 9.2 wt% to 9.8 wt%. When the mass percentage of Si in the iron-silicon-aluminum alloy material is 9.2 wt% to 9.8 wt%, the magnetostriction coefficient of the alloy further approaches zero, and the hysteresis loss is further significantly reduced, which is more conducive to obtaining a lower loss level for the magnetic component under high-frequency operating conditions. For example, the mass percentage of Si in the iron-silicon-aluminum alloy material can be, for example, 9.2 wt%, 9.4 wt%, 9.6 wt%, 9.7 wt%, 9.8 wt%, or any combination thereof.
[0088] In some embodiments of the present invention, the mass percentage of Al element in the iron-silicon-aluminum alloy material is preferably 5.2wt% to 5.6wt%. When the mass percentage of Al element in the iron-silicon-aluminum alloy material is 5.2wt% to 5.6wt%, the permeability decay of the magnetic component under a DC bias magnetic field is further effectively suppressed, and the DC bias characteristics of the magnetic component are further improved. For example, the mass percentage of Al element in the iron-silicon-aluminum alloy material can be, for example, 5.2wt%, 5.3wt%, 5.4wt%, 5.5wt%, 5.6wt%, or any combination thereof.
[0089] In some embodiments of the present invention, within at least 10 incompletely repeating 50μm × 50μm regions of the scanning electron microscope (SEM) image of the cross-section of the magnetic component, the number of first magnetic powder particles with a diameter of 1μm to 10μm is ≥15. This characteristic indicates that the first magnetic powder has sufficiently filled the gaps between the second magnetic powder particles, forming a dense, graded packing structure. The 50μm × 50μm observation region corresponds to an actual area of approximately 2500μm. 2 The presence of more than 15 particles with a diameter of 1-10 μm within this region indicates that the first magnetic powder is uniformly and sufficiently distributed within the magnetic component. By limiting the number of fine particles in this region, the density of the first magnetic powder within the magnetic component can be further characterized, thereby ensuring that the magnetic component exhibits lower losses and higher DC bias performance.
[0090] In some embodiments of the present invention, the magnetic component is prepared by pressing a first powder material and a second powder material, wherein the particle size of the first powder material is ≤10μm and the D50 of the second powder material is >10μm. Specifically, the preparation includes the following steps: mixing the first and second powder materials in a mixing device to achieve a macroscopically uniform distribution; selecting a corresponding pressing mold according to the shape and size of the target magnetic component; cleaning the mold before pressing to remove residual powder and impurities from the mold cavity, and uniformly coating the inner wall of the mold cavity with a release agent to reduce demolding resistance after pressing and reduce surface defects in the product; uniformly loading the uniformly mixed first and second powder materials into the mold cavity according to a predetermined filling amount; placing the mold containing the first and second powder materials in a pressing device and applying a preset molding pressure for pressing. Further, the mixing method can be any one or more combinations of three-dimensional inverted mixing, V-shaped mixing, or mechanical stirring; the mixing time can be appropriately adjusted according to the powder characteristics and equipment type to ensure that the mixing uniformity meets the subsequent pressing requirements. It should be understood that the above examples are merely illustrative and not limiting.
[0091] The particle size of the first powder material is controlled within the range of ≤10μm, which is much smaller than that of the second powder material. This allows it to effectively fill the gaps formed after the particles of the second powder material are stacked, thereby improving the filling coefficient of the magnetic component. Particles with a particle size of ≤10μm are close to the critical size of a single domain and are not easily saturated under a DC bias magnetic field. This helps to delay the overall saturation process of the magnetic component and improve its DC bias performance.
[0092] The D50 of the second powder material is controlled within the range of >10μm, so that it can form a stable particle packing skeleton during the pressing process, providing a suitable filling gap for the first powder material and achieving the densest packing of coarse and fine particles.
[0093] This invention allows for air jet classification of a first powder raw material using conventional classification equipment and instruments in the art. For example, an air jet classifier can be used for dry fine classification of the powder. The specific classification operation includes the following steps: taking an appropriate amount of the first powder raw material sample to be classified and determining the feeding method according to equipment requirements; turning on the air jet classifier and setting appropriate classification parameters, including the classifying wheel speed, the blower airflow, the feeding rate, and the secondary airflow; uniformly feeding the powder to be classified into the classification chamber through the feeding device, allowing the particles to enter the classification zone with the high-speed airflow. Under the combined action of the centrifugal force generated by the classifying wheel and the airflow drag, coarse particles are thrown against the wall and fall to the coarse powder collection port, while fine particles pass through the classifying wheel with the airflow and enter the fine powder collection system, achieving particle size separation; during the classification process, the system pressure difference and classification current are monitored in real time, and the classifying wheel speed or airflow is adjusted according to the target particle size requirement (e.g., ≤10μm) to obtain the desired fine powder product; after classification, the fine and coarse powders are collected separately, and the machine is stopped to clean the residual material inside the equipment. In the above operation, the coordinated adjustment of parameters such as classifying wheel speed, air volume and feed rate will directly affect the classification accuracy and yield. In actual operation, it should be optimized according to the density, dispersibility and target particle size range of the powder to stably obtain fine powder products that meet the particle size requirements.
[0094] This invention allows for the testing of the particle size of a second powder raw material using conventional testing methods and instruments in the art. For example, a laser diffraction particle size analyzer can be used to test the volume-based cumulative particle size distribution of the second powder raw material. The specific testing process includes the following steps: taking an appropriate amount of the second powder raw material sample to be tested, and selecting either wet or dry dispersion according to the instrument requirements; turning on the laser particle size analyzer and setting appropriate measurement parameters, including particle refractive index, shading range, and measurement time; measuring background scattering light on the dispersion medium or air without adding the sample to eliminate environmental interference; introducing the dispersed sample into the instrument's sample cell, allowing the particles to pass through the laser beam irradiation area, and having the detector record the scattering light intensity distribution at different angles; and automatically calculating the particle size distribution to obtain the volume-based cumulative particle size distribution curve. The particle size value corresponding to a cumulative distribution reaching 50% is read from this curve, which is the D50. The results of the two testing methods (wet and dry methods) are similar and within the allowable error range.
[0095] In this embodiment of the invention, in the magnetic component obtained by pressing the first powder raw material and the second powder raw material, particles with a particle size ≤10μm are classified as the first magnetic powder, and particles with a particle size >10μm are classified as the second magnetic powder. Since the D50 of the second powder raw material is >10μm, it may contain particles with a particle size ≤10μm. Therefore, the pressed first magnetic powder actually contains particles from two sources: one is small-diameter particles with a particle size ≤10μm from the first powder raw material, and the other is small-diameter particles with a particle size ≤10μm from the second powder raw material; while the pressed second magnetic powder originates from large-diameter particles with a particle size >10μm from the second powder raw material.
[0096] In this embodiment of the invention, the first powder material may include a silicon-iron alloy core and a coating layer containing one or more elements selected from C, O, and Si; the second powder material may include a silicon-aluminum alloy core and a phosphate coating layer. The first powder material undergoes chemical vapor deposition coating treatment to form a uniform and dense insulating layer on its surface, further controlling the potential increase in eddy current losses introduced by the large specific surface area of the first powder material. The second powder material, after phosphate coating, can further form a high-resistivity insulating layer on its surface, thereby blocking eddy current paths and reducing losses in the magnetic components.
[0097] In some embodiments of the present invention, the iron-silicon alloy core in the first powder raw material and the iron-silicon-aluminum alloy core in the second powder raw material are both prepared using gas atomization. The preparation of alloy powder by gas atomization can employ either vacuum induction melting gas atomization or electrode induction melting gas atomization. Specifically, the preparation includes the following steps: accurately weighing each raw material component according to the composition ratio of the target alloy; placing the prepared raw materials in a melting furnace and heating until completely melted to form a uniform alloy melt; pouring the melted alloy into an intermediate ladle, which is located directly above the atomizing nozzle and has a drain at its bottom, allowing the alloy melt to flow through the drain to form a continuous, fine stream of molten metal, which falls freely under gravity; when the molten metal stream passes through the atomizing nozzle, it is violently impacted and broken by the high-speed airflow; the tiny spherical droplets formed by atomization fly at high speed within the closed atomizing cylinder, exchanging heat with the cooling gas, rapidly cooling and solidifying into a solid powder. The powders prepared by the above-mentioned vacuum induction melting gas atomization method and electrode induction melting gas atomization method have similar properties, and the method can be selected according to actual conditions.
[0098] In some embodiments, chemical vapor deposition (CVD) includes a method for generating a solid coating layer in situ by a chemical reaction of a gaseous precursor on the surface of a first powder material. Specifically, the method includes the following steps: placing an iron-silicon alloy core in a cleaning container and removing impurities such as oil and dust from the powder surface using ultrasonic cleaning or plasma treatment; loading the pretreated magnetic material into the reaction chamber of the CVD apparatus, sealing it, and evacuating it to a predetermined vacuum level; heating and sublimating or vaporizing the solid or liquid precursor material to convert it into a gaseous state; transporting the gaseous precursor to a high-temperature pyrolysis zone, where the precursor molecules are pyrolyzed into reactive monomers at approximately 680°C; introducing the activated gaseous monomers into a deposition chamber containing the pretreated magnetic material, where the gaseous monomers undergo a chemical reaction on the surface of the iron-silicon alloy core at room temperature or an appropriate temperature, and polymerize or deposit in situ to generate a solid coating layer; after deposition, stopping the introduction of the precursor gas, cooling to room temperature under a protective atmosphere, and removing the coated iron-silicon alloy core. Furthermore, the precursor gas can be one or more of the following: pyrene cyclic dimer, trichlorosilane, and hexamethyldisilazane.
[0099] In some embodiments, the phosphate treatment method includes placing a second powder raw material in a treatment solution containing phosphoric acid or phosphate, and generating a metal phosphate insulating coating layer in situ on the powder surface through a chemical reaction. Specifically, the method includes the following steps: sieving and classifying the iron-silicon-aluminum alloy core to be treated to remove coarse particles and agglomerates, and cleaning the iron-silicon-aluminum alloy core to obtain a pretreated iron-silicon-aluminum alloy core; dissolving phosphoric acid or phosphate in deionized water, ethanol, or acetone solution to prepare a passivation treatment solution of a predetermined concentration; adding the pretreated iron-silicon-aluminum alloy core to the passivation treatment solution under a protective atmosphere and heating and stirring; during the reaction, the phosphoric acid reacts chemically with the metal elements on the surface of the iron-silicon-aluminum alloy core, generating a metal phosphate insulating coating layer in situ. Further, the phosphate can be one or more of zinc dihydrogen phosphate, aluminum dihydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate, etc.; the protective atmosphere can be one or more of nitrogen and argon.
[0100] In some embodiments of the present invention, the D50 of the second powder material is 20 μm to 40 μm. By setting the D50 of the second powder material to 20 μm to 40 μm, a better particle size distribution can be formed with the first powder material, thereby reducing the total loss while improving the DC bias performance of the magnetic component. Exemplarily, the D50 of the second powder material can be selected as 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, or a range defined by any two of the above values.
[0101] In some embodiments of the present invention, the mass percentage of the first powder raw material in the first powder raw material and the second powder raw material is 5wt% to 30wt%. When the mass percentage of the first powder raw material in the first powder raw material and the second powder raw material is 5wt% to 30wt%, it can further improve the DC bias performance of the magnetic component and curb the increase of the total loss of the magnetic component. For example, the mass percentage of the first powder raw material in the first powder raw material and the second powder raw material can be selected as 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, or a range defined by any two of the above values.
[0102] In this embodiment of the invention, the pressing pressure is controlled between 200 MPa and 2000 MPa. When the pressure is not lower than 200 MPa, the particles can be further rearranged and subjected to limited plastic deformation, thereby forming a compact with basic strength. When the pressure is not higher than 2000 MPa, a higher density can be obtained while preventing the insulating coating from cracking and peeling off. Exemplarily, the pressing pressure can be, for example, a range of 200 MPa, 700 MPa, 1200 MPa, 1700 MPa, 2000 MPa, or any combination thereof.
[0103] In some embodiments of the present invention, the pressing process takes place for 10 to 60 seconds. By setting the pressing time to 10 to 60 seconds, the present invention ensures sufficient stress transfer and density uniformity while further protecting the integrity of the insulating coating layer. This also provides a precursor with a more uniform structure and a more reasonable residual stress distribution for subsequent annealing, thus contributing to lower losses and higher DC bias performance in the final magnetic assembly. For example, the pressing process time can be within the range of 10 seconds, 20 seconds, 30 seconds, 40 seconds, 50 seconds, 60 seconds, or any combination thereof.
[0104] In some embodiments of the present invention, the raw material system further includes a binder, which includes one or more of epoxy resin, silicone resin, polyimide resin, phenolic resin, and polyvinyl alcohol. The binder, including one or more of epoxy resin, silicone resin, polyimide resin, phenolic resin, or polyvinyl alcohol, can be selected adaptively according to subsequent heat treatment processes or service temperature requirements. The binder can further ensure the integrity of the compact during pressing and further solidify and fix the particle arrangement after annealing, thereby achieving the purpose of maintaining the overall performance of the magnetic component.
[0105] In some embodiments of the present invention, the binder accounts for 0.5wt% to 3wt% of the total mass of the first and second powder raw materials, and is used to temporarily bind the particles during the pressing process and improve the demolding retention effect. Limiting the binder content to the range of 0.5wt% to 3wt% can further ensure the forming strength and operational reliability of the compact, and further avoid excessive dilution of the non-magnetic relative magnetic filling rate, thereby further improving the overall performance of the magnetic component. For example, the proportion of the binder to the total mass of the first and second powder raw materials can be, for example, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 3wt%, or any combination thereof.
[0106] In some embodiments of the present invention, the D50 of the second powder material is preferably 20 μm to 30 μm. When the D50 of the second powder material is 20 μm to 30 μm, the eddy current loss in the magnetic component is more effectively suppressed, and the problem of increased hysteresis loss of the magnetic component due to increased coercivity caused by excessively fine particles in the magnetic component is further avoided. Exemplarily, the D50 of the second powder material can be selected from 20 μm, 22 μm, 25 μm, 27 μm, 30 μm, or a range defined by any two of the above values.
[0107] In some embodiments of the present invention, the mass percentage of the first powder raw material in the first powder raw material and the second powder raw material is preferably 10wt% to 20wt%. When the mass percentage of the first powder raw material in the first powder raw material and the second powder raw material is 10wt% to 20wt%, the DC bias performance of the magnetic component is further improved, while avoiding the problems of enhanced demagnetizing field and increased hysteresis loss caused by excessive small-diameter particles in the magnetic component. Exemplarily, the mass percentage of the first powder raw material in the first powder raw material and the second powder raw material can be selected as 10wt%, 12wt%, 15wt%, 17wt%, 20wt%, or a range defined by any two of the above values.
[0108] In some embodiments of the present invention, the pressing pressure is preferably 1000 MPa to 1500 MPa. When the pressing pressure is 1000 MPa to 1500 MPa, the first powder material can more effectively fill the gaps formed by the accumulation of the second powder material, further increasing the density of the compact, which can further reduce the loss of the magnetic component and improve its dimensional uniformity after annealing; at the same time, the pressure is still below the insulation layer rupture threshold, further maintaining the integrity of the insulation system and the high-frequency low-loss characteristics. Exemplarily, the pressing pressure can be, for example, a range of 1000 MPa, 1250 MPa, 1500 MPa, 1750 MPa, 2000 MPa, or any combination thereof.
[0109] In some embodiments of the present invention, after pressing, the pressed product is further subjected to annealing at a temperature of 600℃ to 850℃ for a time of 0.5h to 3h. After pressing, the pressed body contains residual stress between particles, local porosity, and interfacial instability. Annealing at 600℃ to 850℃ promotes further microscopic diffusion and stress relaxation at particle contact points. The 0.5h to 3h holding time further improves tissue homogenization, stabilizing the main framework composed of large-particle-size second magnetic powder and the filling structure formed by fine-particle-size first magnetic powder. This further maintains the compactness of the pressed body and improves the continuity of the magnetic circuit, resulting in a more stable structural state and more consistent batch forming results for the obtained magnetic components under high-frequency operating conditions.
[0110] In some embodiments of the present invention, the annealing process can be carried out under an inert atmosphere, a reducing atmosphere, or a low-oxygen atmosphere to further reduce oxidation and maintain the stability of the coating layer and the core structure. In another possible embodiment, the annealing heating and cooling rates can be set according to the size of the pressed body and the furnace loading to further improve thermal stress concentration. By coordinating the above temperature and time windows, stress release, particle contact interface rearrangement, and partial thermal decomposition or curing transformation of the binder can be better achieved within the magnetic component without significantly damaging the pressed structure, thereby obtaining a structurally stable magnetic component. It should be understood that the above examples are merely illustrative and not limiting.
[0111] The density of magnetic components can be tested using conventional testing methods and instruments in the art, such as the Archimedes' displacement method specified in GB / T 3850-2015 "Method for Determination of Density of Dense Sintered Metal Materials and Hard Alloys". Specifically, the sample is weighed in air, then immersed in a liquid and weighed again. The volume of the sample is calculated from the mass difference, thus obtaining the measured density. The measured density is then divided by the theoretical density of the material system and multiplied by 100% to obtain the density.
[0112] The permeability of magnetic components can be tested using conventional testing methods and instruments in the art. For example, the measurement can be performed using a precision LCR analyzer at a test frequency of 100kHz, referring to GB / T 3658-2022 "Method for Measurement of Magnetic Properties of Soft Magnetic Metallic Materials and Powder Metallurgical Materials in the Frequency Range of 20Hz~100kHz". Specifically, a coil with a certain number of turns is wound around the magnetic component to form a ring-shaped test sample. The sample is connected to the test terminal of the LCR analyzer, and the inductance value of the sample is read at a test frequency of 100kHz. The permeability of the sample is calculated from the inductance value based on the effective magnetic path length, effective cross-sectional area, and number of coil turns.
[0113] The embodiments of this invention can test the loss of magnetic components using conventional testing methods and instruments in the art. For example, the standard GB / T 3658-2022 "Method for Measurement of Magnetic Properties of Soft Magnetic Metallic Materials and Powder Metallurgical Materials in the Frequency Range of 20Hz~100kHz" can be referenced, and a BH analyzer can be used to measure the loss at a test frequency of 100kHz and a magnetic flux density of 50mT. Specifically, a primary excitation coil and a secondary induction coil are wound around the magnetic component and connected to the test circuit of the BH analyzer. The test frequency is set to 100kHz, and an alternating magnetic field is applied through the excitation coil to make the working magnetic flux density of the magnetic component reach 50mT. The magnetic induction intensity is obtained by integrating the voltage signal induced by the secondary coil, and then the loss value of the magnetic component per unit volume or per unit mass can be directly read or calculated by the BH analyzer.
[0114] The embodiments of the present invention can test the DC bias superposition characteristics of magnetic components using conventional testing methods and instruments in the art. For example, a DC bias current source can be used in conjunction with an LCR analyzer for measurement. Specifically, after the magnetic component is wound into a test coil, it is connected to the test circuit. A gradually increasing DC bias current is applied to the coil by the DC bias current source, causing a superimposed DC magnetic field to be generated inside the magnetic component. At the same time, the permeability of different magnetic components under the same DC bias current is measured in real time at a specified test frequency using an LCR analyzer, thereby characterizing the permeability maintenance ability and saturation characteristics of the magnetic component under DC bias conditions.
[0115] The technical solution of the present invention will be further described below with reference to specific embodiments.
[0116] Example 1
[0117] The magnetic component in this embodiment is prepared by the following method:
[0118] 1) Iron-silicon alloy ingots containing 3 wt% Si and 97 wt% Fe were gas-atomized and sieved to obtain iron-silicon alloy cores with a particle size ≤10 μm. The iron-silicon alloy cores with a particle size ≤10 μm were placed in a tube furnace, pure nitrogen was introduced to purge air, and the temperature was raised to 400°C. Then, a mixed gas was introduced for chemical deposition coating for 4 hours, forming a coating layer with a thickness of 120 nm on the surface of the iron-silicon alloy cores. The iron-silicon alloy cores with the coating layer were washed, dried, and sieved to obtain the first powder raw material with a particle size of 5 μm.
[0119] The mixed gas consists of tetraethoxysilane (TEOS) vapor and argon carrier gas in a volume ratio of 1:4.
[0120] The coating layer on the surface of the aforementioned iron-silicon alloy core contains 0.5% C, 5.5% O, and 15% Si.
[0121] 2) An iron-silicon-aluminum alloy ingot containing 89 wt% Fe, 9.6 wt% Si, and 5.4 wt% Al was gas-atomized to obtain an iron-silicon-aluminum alloy core.
[0122] A 1 mol / L phosphoric acid solution was added to anhydrous ethanol heated to 50°C and stirred at 400 rpm for 5 min to obtain a phosphoric acid ethanol solution. Then, zinc dihydrogen phosphate powder was added and ultrasonically dispersed until the zinc dihydrogen phosphate powder was completely dissolved in the phosphoric acid ethanol solution. The interval between each ultrasonic dispersion treatment was 1 min, and the duration of each treatment was 4 min, resulting in a zinc dihydrogen phosphate ethanol mixed solution with a pH of 2-3. The mass ratio of phosphoric acid solution to anhydrous ethanol was 1:120, and the mass ratio of zinc dihydrogen phosphate powder to phosphoric acid ethanol solution was 1:30.
[0123] A ferrosilicon-aluminum alloy core was added to a rotary reactor. A protective atmosphere of 95% argon and 5% nitrogen was introduced into the reactor, followed by the addition of the aforementioned zinc dihydrogen phosphate-ethanol mixture. The stirring speed inside the rotary reactor was 400 r / min. The reactor was heated to 150°C using a microwave heating device, and a solvent reflux mechanism was added. The reaction time was 30 min. After washing, drying, and sieving, a second powder raw material with a D50 of 30 μm was obtained. The mass ratio of the ferrosilicon-aluminum alloy core to the zinc dihydrogen phosphate-ethanol mixture was 1:1.5.
[0124] 3) Mix the first powder raw material with the second powder raw material, making the first powder raw material account for 10 wt% of the total mass of the first and second powder raw materials. Add the first and second powder raw materials to a V-type mixer and mix at 30 rpm for 2 hours. Then add 1.5 wt% of epoxy resin binder (based on the total mass of the first and second powder raw materials) and continue mixing at 30 rpm for 0.5 hours until homogeneous. Load the mixed powder into a mold and press it at 1200 MPa for 30 seconds to obtain a ring-shaped magnetic component green body with an outer diameter of 26.9 mm, an inner diameter of 14.5 mm, and a height of 11.2 mm.
[0125] 4) The pressed green blank is annealed in a nitrogen atmosphere and held at 700℃ for 2 hours to obtain a magnetic component.
[0126] Example 2
[0127] This embodiment is basically the same as Embodiment 1, except that: in this embodiment, the first powder raw material accounts for 20wt% of the total mass of the first powder raw material and the second powder raw material, and the other process parameters are the same.
[0128] Example 3
[0129] This embodiment is basically the same as Embodiment 1, except that: in this embodiment, the first powder raw material accounts for 5% of the total mass of the first powder raw material and the second powder raw material, and the remaining process parameters are the same.
[0130] Example 4
[0131] This embodiment is basically the same as Embodiment 1, except that: the first powder raw material accounts for 30% of the total mass of the first powder raw material and the second powder raw material, and the remaining process parameters are the same.
[0132] Example 5
[0133] This embodiment is basically the same as Embodiment 1, except that: the particle size of the first powder raw material in this embodiment is 1μm, the D50 of the second powder raw material is 20μm, and the other process parameters are the same.
[0134] Example 6
[0135] This embodiment is basically the same as Embodiment 1, except that: the particle size of the first powder raw material in this embodiment is 10μm, the D50 of the second powder raw material is 40μm, and the other process parameters are the same.
[0136] Example 7
[0137] This embodiment is basically the same as embodiment 1, except that: in this embodiment 1), the mixed gas is composed of hexamethyldisilazane vapor and nitrogen carrier gas in a volume ratio of 1:5; the first coating layer contains 0%C, 3%O and 9%Si.
[0138] Furthermore, in this embodiment 2), the phosphate is ammonium dihydrogen phosphate;
[0139] Furthermore, the coating thickness of the first powder raw material is 0.2 μm, the coating thickness of the second powder raw material is 0.5 μm, and the other process parameters are the same.
[0140] Example 8
[0141] This embodiment is basically the same as Embodiment 1, except that: in this embodiment 1), the mixed gas consists of hexamethyldisiloxane vapor and argon carrier gas in a volume ratio of 1:6; the first coating layer contains 1% C, 8% O, and 20% Si;
[0142] Furthermore, in this embodiment 2), the phosphate is ammonium dihydrogen phosphate;
[0143] Furthermore, the coating thickness of the first powder raw material is 50 nm, the coating thickness of the second powder raw material is 0.1 μm, and the other process parameters are the same.
[0144] Example 9
[0145] This embodiment is basically the same as Embodiment 1, except that: in this embodiment, the mass proportions of Fe and Si elements in the iron-silicon alloy material are 85% and 15% respectively, and the mass proportions of Fe, Si, and Al elements in the iron-silicon aluminum alloy material are 80%, 10%, and 10% respectively, with the remaining process parameters being the same.
[0146] Example 10
[0147] This embodiment is basically the same as Embodiment 1, except that: in this embodiment, the mass ratio of Fe and Si elements in the iron-silicon alloy material is 95% and 5% respectively, and the mass ratio of Fe, Si and Al elements in the iron-silicon aluminum alloy material is 90%, 5% and 5% respectively, with the remaining process parameters being the same.
[0148] Example 11
[0149] This embodiment is basically the same as Embodiment 1, except that in step 3), the first powder raw material and the second powder raw material are added to a three-dimensional mixer and mixed at 20 rpm for 4 hours. Then, 0.5 wt% of silicone resin binder (based on the total mass of the first and second powder raw materials) is added, and mixing continues for 0.5 hours until homogeneous. The mixed powder is then loaded into a mold and pressed at 200 MPa for 10 seconds to obtain a magnetic component green body. The annealing temperature is 600℃, and the holding time is 3 hours. The remaining process parameters are the same.
[0150] Example 12
[0151] This embodiment is basically the same as Embodiment 1, except that in step 3), the first powder raw material and the second powder raw material are added to a three-dimensional mixer and mixed at 60 rpm for 0.5 hours. Then, 3 wt% of phenolic resin binder (based on the total mass of the first and second powder raw materials) is added, and mixing continues for another 0.5 hours until homogeneous. The mixed powder is then loaded into a mold and pressed at 1000 MPa for 60 seconds to obtain a green compact of the magnetic component. The annealing temperature is 850°C, and the holding time is 0.5 hours. The remaining process parameters are the same.
[0152] Example 13
[0153] This embodiment is basically the same as Embodiment 1, except that: both the iron-silicon alloy core and the iron-silicon-aluminum alloy core are coated using a phosphate coating process, and the other process parameters are the same.
[0154] Comparative Example 1
[0155] This embodiment is basically the same as Embodiment 1, except that: only the second powder raw material with a D50 of 30μm is used in the preparation process, and the first powder raw material is not added. The other process parameters are the same.
[0156] Comparative Example 2
[0157] This embodiment is basically the same as Embodiment 1, except that: only the first powder raw material with a particle size of 5μm is used in the preparation process, and no second powder raw material is added, while the other process parameters are the same.
[0158] Comparative Example 3
[0159] This embodiment is basically the same as Embodiment 1, except that: a first powder raw material with a particle size of 15μm and a second powder raw material with a D50 of 20μm are used in the preparation process, while the other process parameters are the same.
[0160] Test case
[0161] (I) Performance Comparison of Magnetic Components
[0162] The Archimedes' displacement method was used in accordance with GB / T3850-2015, "Method for Determination of Density of Dense Sintered Metallic Materials and Hard Alloys". Specifically, the sample was weighed in air, then immersed in the liquid and weighed again. The volume of the sample was calculated from the mass difference, and the measured density was obtained. The measured density was then divided by the theoretical density of the material system and multiplied by 100% to obtain the density.
[0163] Referring to GB / T3658-2022 "Method for Measurement of Magnetic Properties of Soft Magnetic Metallic Materials and Powder Metallurgical Materials in the Frequency Range of 20Hz~100kHz", a precision LCR analyzer was used to perform measurements at a test frequency of 100kHz. Specifically, a magnetic component was wound with a coil of a certain number of turns to form a ring-shaped test sample. The sample was connected to the test terminal of the LCR analyzer, and the inductance value of the sample was read at a test frequency of 100kHz. Based on the effective magnetic path length, effective cross-sectional area, and number of coil turns, the permeability of the sample was calculated from the inductance value.
[0164] While ensuring that the magnetic permeability is 70 H / m in all embodiments, the measurement was performed using a BH analyzer at a test frequency of 100 kHz and a magnetic flux density of 50 mT, in accordance with GB / T3658-2022 "Method for Measurement of Magnetic Properties of Soft Magnetic Metallic Materials and Powder Metallurgical Materials in the Frequency Range of 20 Hz to 100 kHz". Specifically, the magnetic component was wound with a primary excitation coil and a secondary induction coil, which were then connected to the test circuit of the BH analyzer. The test frequency was set to 100 kHz, and an alternating magnetic field was applied through the excitation coil to make the working magnetic flux density of the magnetic component reach 50 mT. The magnetic induction intensity was obtained by integrating the voltage signal induced by the secondary coil, and then the loss value of the magnetic component per unit volume or per unit mass was directly read by the BH analyzer.
[0165] To ensure that the permeability in all embodiments is 70 H / m, a DC bias current source was used in conjunction with an LCR analyzer for measurement. Specifically, based on the method described above for testing the permeability of magnetic components, the permeability of different embodiments and comparative examples under the same DC bias current was tested to characterize the permeability maintenance capability of the magnetic components under DC bias conditions. Specifically, the test frequency was set to 100 kHz and the AC level to 50 mVrms. The initial inductance L0 of each material at 0 A and the inductance L under a constant bias of 5 A were measured respectively. After applying the bias and stabilizing the reading for 2-3 seconds, the attenuation rate was calculated. .
[0166] The embodiments and comparative examples were characterized using the above measurement methods, and the obtained data are shown in Table 1. In the embodiments, if the loss of the magnetic component is less than 240 mW / cm², then... 3 If its DC bias performance is higher than 64%, then this embodiment can be considered to have both low loss and excellent DC bias characteristics.
[0167]
[0168] (II) Microscopic characterization of magnetic components
[0169] Take the magnetic component samples prepared in Example 1 and Comparative Example 1, respectively, clamp both ends of the sample with pliers, apply appropriate external force to break them off, and expose the internal cross-section for subsequent morphological observation or performance testing. The cross-section is not polished to avoid fine particles from falling off and affecting morphological observation.
[0170] The cross-sections of the magnetic components of Example 1 and Comparative Example 1 were observed using a scanning electron microscope (SEM). At a magnification of at least 500x, at least 10 non-repeating 50μm × 50μm observation areas were selected on the cross-sections of the magnetic components of Example 1 and Comparative Example 1. The number of particles with a diameter of 1~10μm in each area was counted. If the number of particles within this diameter range was ≥10, the magnetic component was considered to meet the requirements of the present invention.
[0171] Figure 1 , Figure 2 , Figure 3 The images shown are scanning electron microscope (SEM) images of the cross-section of the magnetic component in Example 1 at different magnifications. Figure 4The image shown is a scanning electron microscope (SEM) image of the cross-section of the magnetic component in Comparative Example 1 at 200x magnification. Ten randomly selected, non-repeating 50μm × 50μm observation areas were chosen from the cross-section of the magnetic component in Example 1. The number of particles with a diameter of 1–10μm in each area was 18, 16, 17, 21, 15, 23, 21, 20, 17, and 22, respectively, all meeting the requirement that the number of particles with a diameter of 1–10μm ≥ 10. However, under the same conditions, Comparative Example 1 showed 7, 3, 9, 1, 5, 8, 2, 6, 4, and 7 particles with a diameter of 1–10μm, respectively, failing to meet the requirement of ≥ 10 particles with a diameter of 1–10μm.
[0172] The above results confirm that in Example 1, the first magnetic powder effectively filled the gaps between the second magnetic powders, forming a dense gradation and packing structure.
[0173] (III) Characterization of the physicochemical properties of magnetic components
[0174] The thickness of the insulating coating layer on the surface of magnetic particles is measured non-destructively using a magnetic thickness gauge. The specific testing steps include: turning on the magnetic thickness gauge; calibrating the gauge using a standard sheet; selecting multiple measurement points evenly distributed on the sample surface, ensuring the distribution of these points represents the overall thickness of the coating layer; placing the probe vertically and stably on each measurement point, avoiding tilting which could affect measurement accuracy; and reading the measurement result after the displayed value stabilizes. Each measurement point should be measured multiple times, typically at least three times, and the average value is taken as the thickness at that point.
[0175] This invention allows for the testing of the elemental composition and distribution of magnetic powders using conventional testing methods and instruments in the art. For example, a scanning electron microscope (SEM) equipped with an energy-dispersive X-ray spectrometer (EDS) can be used for qualitative and semi-quantitative analysis of the micro-area elemental composition of the magnetic powder. The specific testing process includes the following steps: fixing the magnetic powder sample to be tested on a sample stage coated with conductive adhesive; turning on the SEM power supply and EDS software; placing the prepared sample stage into the sample exchange chamber of the SEM, closing the chamber door, and performing a vacuum operation; obtaining a clear image of the sample surface morphology by adjusting the focus, astigmatism, brightness, and contrast; and using the following analysis modes: point analysis, line scan analysis, and area distribution analysis; and performing EDS acquisition, elemental confirmation, and quantitative analysis. The test results of the three modes—point analysis, line scan analysis, and area distribution analysis—can corroborate each other within the allowable error range.
Claims
1. A magnetic component, characterized in that, Including magnetic powder; The magnetic powder includes a first magnetic powder and a second magnetic powder; The particle size of the first magnetic powder is ≤10μm; The particle size of the second magnetic powder is >10 μm; In the cross-sectional scanning electron microscope image of the magnetic component, the number of particles of the first magnetic powder with a particle size of 1μm to 10μm is ≥10 in at least 10 non-completely repeating 50μm×50μm regions.
2. The magnetic component according to claim 1, characterized in that, The first magnetic powder includes a first core and a first coating layer disposed on at least a portion of the surface of the first core; And / or, the second magnetic powder includes a second core and a second coating layer disposed on at least a portion of the surface of the second core; And / or, the particle size range of the first magnetic powder is 1 μm to 10 μm; And / or, the D50 of the second magnetic powder is 20μm~40μm.
3. The magnetic component according to claim 2, characterized in that, The first core comprises at least one of iron-silicon alloy material and iron-silicon-aluminum alloy material; And / or, the second core comprises an iron-silicon-aluminum alloy material; And / or, the first coating layer includes one or more elements selected from C, O, and Si; And / or, the first coating layer comprises phosphate; And / or, the second coating layer comprises phosphate; And / or, the thickness of the first coating layer is 50nm~500nm; And / or, the thickness of the second coating layer is 0.1 μm to 0.5 μm.
4. The magnetic component according to claim 3, characterized in that, The mass percentage of Fe in the iron-silicon alloy material is 85wt%~98wt%; And / or, the mass percentage of Si in the iron-silicon alloy material is 2wt%~15wt%; And / or, the mass percentage of Fe in the iron-silicon-aluminum alloy material is 80wt%~90wt%; And / or, the mass percentage of Si element in the iron-silicon-aluminum alloy material is 5wt%~12wt%; And / or, the mass percentage of Al element in the iron-silicon-aluminum alloy material is 5wt%~12wt%.
5. The magnetic component according to claim 4, characterized in that, The mass percentage of carbon element in the first coating layer is 0 wt% to 1 wt%. And / or, the mass percentage of O element in the first coating layer is 3wt%~8wt%; And / or, the mass percentage of Si element in the first coating layer is 9wt%~20wt%; And / or, the mass percentage of Fe in the iron-silicon alloy material is 95.2 wt% to 97.2 wt%; And / or, the mass percentage of Si element in the iron-silicon alloy material is 2.8wt%~4.8wt%; And / or, the mass percentage of Fe in the iron-silicon-aluminum alloy material is 84.6 wt% to 85.6 wt%; And / or, the mass percentage of Si element in the iron-silicon-aluminum alloy material is 9.2wt%~9.8wt%; And / or, the mass percentage of Al element in the iron-silicon-aluminum alloy material is 5.2wt%~5.6wt%.
6. The magnetic component according to claim 1, characterized in that, In the scanning electron microscope image of the cross-section of the magnetic component, within at least 10 non-completely repeating 50μm×50μm regions, the number of particles of the first magnetic powder with a particle size of 1μm to 10μm is ≥15.
7. A method for preparing the magnetic component according to claims 1-6, characterized in that, The process includes the following steps: pressing a raw material system comprising a first powder raw material and a second powder raw material to obtain the magnetic component; the particle size of the first powder raw material is ≤10μm; and the D50 of the second powder raw material is >10μm.
8. The method for preparing the magnetic component according to claim 7, characterized in that, The D50 of the second powder raw material is 20μm~40μm; And / or, the first powder raw material accounts for 5wt% to 30wt% of the total mass of the first powder raw material and the second powder raw material; And / or, the processing pressure of the pressing process is 200MPa~2000MPa; And / or, the processing time for the pressing process is 10s to 60s.
9. The method for preparing the magnetic component according to claim 8, characterized in that, The raw material system also includes a binder, which includes one or more of epoxy resin, silicone resin, polyimide resin, phenolic resin, and polyvinyl alcohol. And / or, the raw material system further includes a binder, the binder accounting for 0.5wt% to 3wt% of the total mass of the magnetic powder; And / or, the D50 of the second powder raw material is 20μm~30μm; And / or, the first powder raw material accounts for 10wt% to 20wt% of the total mass of the first powder raw material and the second powder raw material; And / or, the processing pressure of the pressing process is 1000MPa~1500MPa.
10. The method for preparing the magnetic component according to claim 8 or 9, characterized in that, After the pressing process, the product is further subjected to an annealing process at a temperature of 600℃ to 850℃ for a time of 0.5h to 3h.